Analysis of the reading ability of low vision students at the primary school teacher education, PGRI Ronggolawe University - Pujiastuti, Arik Umi; Wiratsiwi , Wendri (JURNAL PENDIDIKAN DASAR NUSANTARA, 2024)
Abstrak: Reading is one of the language skills a person has. When someone experiences problems with their sense of sight, it will definitely affect their reading ability. One of the disorders in the sense of sight is Low Vision. This research aims to describe the reading abilities of elementary school teacher education students with low vision. In learning practices at higher education institutions, low vision students have the same rights as regular students. This research method is a case study, and the research data was collected using interview and observation techniques using interview sheet instruments and observation guide sheets. The data that has been collected is analyzed descriptively qualitatively. Based on the results of interviews and observations, the type of letters that can be read are Times New Roman, Calibri, and Arial. The results of interviews and observations show that the three letters are size 12, spacing 1, 1.5, and 2, 2.5. and 3 spaces 1, 1.5, and 2 are not readable from any distance. The three letters, with sizes 14 and 16, bold, space 1, 1.5, and 2, black, white background, are not legible, but they are legible at a distance of 10 to 15 cm when using spaces 2, 2.5, and 3 and students occasionally spell and activities are carried out in outdoor. When indoors, students need more time to carry out these activities. Research subjects were also unable to read paragraphs consisting of three or more sentences. The reading activities of research subjects are also influenced by the light around them.